การจัดทำฐานข้อมูลทางกุมารศัลยศาสตร์ของโรงพยาบาลสงขลานครินทร์ : ศึกษาเฉพาะความพิการแต่กำเนิดของทางเดินอาหารและช่องท้อง - ศักดา ภัทรภิญโญกุล (มหาวิทยาลัยสงขลานครินทร์)
The purposes for the study are (1) to comply and analyse the data of the patients at Songklanagarind hospital, (2) to design the database of congenital anomalies of the G.I-tract and abdomen, (3) to implement the database of the congenital anomalies for the treatment and teaching by studying quantitatively and qualitatively. Comply the primary data and secondary data by using software Foxpro version 2.6 for managing the database. The outcome of this study can be analysed and designed as followed ; (I) data for the group of diseases, (2) data for organ systems, (3) data for individual organ, (4) the disease data which can be designed for the database fles which are patient details, vital statisties, symptoms and signs physical examinations and laboratory investigations, specifc investigations, final diagnosis and records of treatments, the record of complications followed treatments and the records of follow up. There are four levels of implementation, (1) to implement for patient statistic, (2) to implement for primary working system, (3) to implement for patient care, (4) to implement for the education. In conclusion, this systematically complying database is benefcial for pediatric surgeons as a guide for medical planning and effective treatment of pediatric G.I malformation in the future.